High Resolution In Vivo Bioluminescent Imaging for the Study of Bacterial Tumour Targeting - Cronin, Michelle (Public Library of Science, 2012)
The ability to track microbes in real time in vivo is of enormous value for preclinical investigations in infectious disease or gene therapy research. Bacteria present an attractive class of vector for cancer therapy, possessing a natural ability to grow preferentially within tumours following systemic administration. Bioluminescent Imaging (BLI) represents a powerful tool for use with bacteria engineered to express reporter genes such as lux. BLI is traditionally used as a 2D modality resulting in images that are limited in their ability to anatomically locate cell populations. Use of 3D diffuse optical tomography can localize the signals but still need to be combined with an anatomical imaging modality like micro-Computed Tomography (μCT) for interpretation. In this study, the non-pathogenic commensal bacteria E.coli K-12 MG1655 and Bifidobacterium breve UCC2003, or Salmonella Typhimurium SL7207 each expressing the luxABCDE operon were intravenously (IV) administered to mice bearing subcutaneous (s.c) FLuc-expressing xenograft tumours. Bacterial lux signal was detected specifically in tumours of mice post IV-administration and bioluminescence correlated with the numbers of bacteria recovered from tissue. Through whole body imaging for both lux and FLuc, bacteria and tumour cells were co-localised. 3D BLI and μCT image analysis revealed a pattern of multiple clusters of bacteria within tumours. Investigation of spatial resolution of 3D optical imaging was supported by ex vivo histological analyses. In vivo imaging of orally-administered commensal bacteria in the gastrointestinal tract (GIT) was also achieved using 3D BLI. This study demonstrates for the first time the potential to simultaneously image multiple BLI reporter genes three dimensionally in vivo using approaches that provide unique information on spatial locations.